1984
DOI: 10.1111/j.1471-0528.1984.tb04738.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of saliva, plasma unconjugated and plasma total oestriol levels throughout normal pregnancy

Abstract: Saliva unconjugated, plasma unconjugated and plasma total oestriol (E3) levels were measured longitudinally, by radioimmunoassay, in 25 normal women from 13 weeks gestation until delivery. The increase in salivary unconjugated oestriol closely paralleled that of plasma unconjugated oestriol and to a lesser extent that of plasma total oestriol. In each patient the percentage value of salivary E3/plasma unconjugated E3 x 100 was virtually constant throughout pregnancy but this percentage varied from one patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…We found that estriol was quantitatively the most abundant free estrogen in antepartum saliva. Salivary estriol increased linearly during late gestation and the concentrations seen at all time points were within expected ranges based on other studies that have successfully measured estriol in saliva [19,20,22,63]. Suri et al [63] used the Salimetrics EIA, the same EIA employed in the present work.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We found that estriol was quantitatively the most abundant free estrogen in antepartum saliva. Salivary estriol increased linearly during late gestation and the concentrations seen at all time points were within expected ranges based on other studies that have successfully measured estriol in saliva [19,20,22,63]. Suri et al [63] used the Salimetrics EIA, the same EIA employed in the present work.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have used either mixed longitudinal (e.g., [22,41,78]) or cross-sectional data collection [7,19,25,40]. Mixed longitudinal designs have the potential to falsely inflate correlations by introducing dependencies among pairs of observations [79], but no obvious differences in the size of the correlations obtained are evident between the studies that have used cross-sectional vs longitudinal [20] or mixed longitudinal sampling. The low correlations found in the present work as well as these previous studies suggest that low correlations between serum and saliva measurements may not be atypical during late pregnancy and the early postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the salivary concentrations of different hormones have been correlated with their serum levels in humans [2,5,13,18,19,21], to our knowledge, salivary hormonal levels have never been measured in mice.…”
Section: Discussionmentioning
confidence: 99%
“…9 Keadaan tersebut juga diketahui pada manusia bahwa keadaan pubertas, kehamilan dan kontrasepsi hormonal dapat ditandai adanya peningkatan kadar hormon steroid dalam plasma selanjutnya dapat dideteksi di dalam cairan sulkus gingival dan saliva. 22,23 Terjadinya inflamasi kemungkinan karena hormon menginduksi perubahan mikroflora pada gingiva crevice. 24 Sejumlah penelitian menunjukkan bahwa hormon seks diduga memiliki peran penting dalam inflamasi kronis penyakit periodontal.…”
Section: Kontrasepsiunclassified